Obtaining of high purity amorphous silicon dioxide from rice husk - Gridneva, Tatiana; Kravchenko, Alexander; Barsky, Vadim; Gurevina, Natalia (Publishing House of Lviv Polytechnic National University, 2016)
Using maximum extraction of carbon-containing components the content of amorphous silicon dioxide was increased in the rice husk solid residue. In accordance with the hypothesis about the mechanism of extracting carbon-containing components from rice husk by liquid extractants, proper extractants were selected. The effect of main technological factors including a process temperature, time and concentration of the extractants was determined. Внаслідок максимального вилучення карбон-вмісних компонентів, підвищено вміст аморфного силіцій(IV) оксиду у твердому залишку рисового лушпиння. Вибрано екстрагенти відповідно до гіпотези про механізм екстрагування карбонвмісних компонентів з рисового лушпиння рідкими екстрагентами. Встановлено вплив основних технологічних чинників: температура, час процесу та концентрація екстрагенту.
Одержання аморфного силіцій(IV) оксиду підвищеної чистоти із рисового лушпиння
Keywords: amorphous silicon dioxide; rice husk; extraction; lignin; cellulose; mechanism; hypothesis; аморфний силіцій(IV) оксид; рисове лушпиння; екстрагування; лігнін; целюлоза; механізм; гіпотеза